A Citizen Science Community of Practice: Relational Patterns Contributing to Shared Practice. (25th January 2022) - Sbrocchi, Carla; Pecl, Gretta; van Putten, Ingrid; Roetman, Philip
Citizen science networks are a recent global phenomenon, with associated communities of practice that have emerged to support growth in the field and the development of practices. Effective communities of practice are dependent on the interactions from the social network underpinning the community. We examined the Australian citizen science practitioner network, using a combined social network analysis and survey approach. Our goal was to understand the structure and characteristics of this network, to establish who participates in this network, where and how interactions occur, and explore what participation achieves for the users. The Australian citizen science practitioner network has benefited from face-to-face citizen science events to make important connections that have been leveraged to benefit other working relationships and positive outcomes, especially for early-career practitioners and women within the network. How the community of practice continues to navigate successful knowledge exchange across society and science, whether through interactions in face-to-face or virtual settings, will need to be addressed as the community continues to grow in scope and size. In particular, the network will need to consider supporting key individuals who play important bridging functions across the citizen science practitioner network. The emergence of transdisciplinarity amongst those working in citizen science is a promising property of this learning community that is worth working strategically to maintain.